2018
DOI: 10.1080/14767058.2017.1421927
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cytoglobin (CYGB) serum levels in normal and preeclamptic pregnancies

Abstract: Serum CYGB levels were significantly higher in patients with EO-PE and LO-PE as compared to healthy pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In severe PE with proteinuria >3 g/L showed that the amount of proteinuria is not associated with severe PE, although proteinuria is detected, prematurity may occur [29]. Serum cytoglobin was significantly more effective and higher in patients with early-onset preeclampsia (EO-PE) and slow onset of preeclampsia (LOPE), compared with healthy pregnant women [30]. Uric acid with proteinuria can identify perinatal risk with high risk with gestational hypertension in women [31].…”
Section: Biomarker In Pementioning
confidence: 99%
“…In severe PE with proteinuria >3 g/L showed that the amount of proteinuria is not associated with severe PE, although proteinuria is detected, prematurity may occur [29]. Serum cytoglobin was significantly more effective and higher in patients with early-onset preeclampsia (EO-PE) and slow onset of preeclampsia (LOPE), compared with healthy pregnant women [30]. Uric acid with proteinuria can identify perinatal risk with high risk with gestational hypertension in women [31].…”
Section: Biomarker In Pementioning
confidence: 99%
“…These complications are inversely proportional to the experience of the person who applies the method. Amniotic fluid leak, vaginal bleeding, uterine contractions, chorioamnionitis, sampling failure, miscarriage, fetal loss and possible fetal injuries are among the complications of amniocentesis [3] .…”
Section: Introductionmentioning
confidence: 99%
“…This imbalance between proinflammatory and anti-inflammatory regulatory cytokines is associated with placental ischemia in preeclampsia during pregnancy. This imbalance worsens as pregnancy progresses, further complicating pregnancy (7). Growth suppression-specific protein 6(Gas6) is a secreted protein encoded by a growth suppressionspecific gene, which is widely found in a variety of tissues, such as the small intestine, lung, kidney, placenta and endothelial cells, and can also be detected in human serum or plasma.…”
Section: Introductionmentioning
confidence: 99%